Characterization and Synergistic Antimicrobial Evaluation of Lipopeptides from Bacillus amyloliquefaciens Isolated from Oil-Contaminated Soil - Pratiwi Sudarmono; Ahmad Wibisana; Lira W. Listriyani; Saleha Sungkar (International Journal of Microbiology)
Lipopeptides show great potential for biomedical application. Several lipopeptides exhibit narrow and broad-spectrum inhibition activities. The aim of the study is to characterize the lipopeptides produced by B. amyloliquefaciens strain MD4-12 and evaluate the synergistic antimicrobial activity in combination with a conventional antibiotic against Gram-negative bacteria. B. amyloliquefaciens strain MD4-12 was isolated from oil-contaminated soil. The isolate was cultivated in McKeen medium, and the lipopeptides were isolated by precipitation and extraction with methanol. Characterization of the lipopeptides by ESI-MS gave nine mass ion peaks with m/z 994–1072, resulted from protonating of the main ions in [M + H]+ and [M + Na]+ ion form. These mass ion peaks attributed to surfactin homologs. By tandem mass spectrometry, five variants of surfactin with the same amino acid sequence in peptide moiety could be revealed. The peptide moiety contains seven amino acids identified as Glu-Leu/Ile-Leu-Val-Asp-Leu-Leu/Ile while the fatty acid moiety comprises a different length of chain from C12 to C16. Surfactin showed antibacterial activity against various Gram-positive and Gram-negative bacteria. Combination surfactin with ampicillin showed a synergistic effect against P. aeruginosa ATCC 27853.